Analisis Motivasi Kerja dalam Upaya Meningkatkan Produktivitas Pegawai pada Kantor Kelurahan Ciganjur Jakarta Selatan - Apriliani, Anggy; Sina, Ibnu (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to analyze work motivation in improving employee productivity at the Ciganjur Urban Village Office, South Jakarta. Work motivation is an essential factor that encourages employees to perform optimally to achieve organizational goals. This research focuses on identifying the dominant factors influencing work motivation and their implementation in enhancing employee productivity. The study employs a descriptive qualitative approach conducted at the Ciganjur Urban Village Office, Jagakarsa District, South Jakarta. Data were collected through interviews, observations, and documentation with informants consisting of employees and the village head. The data were analyzed through data reduction, data display, and conclusion drawing, while the validity of the findings was tested using source and method triangulation, as well as SWOT analysis. The results indicate that employees’ work motivation is generally good but still requires improvement in aspects such as ambition, perseverance, initiative, and time management. The main driving factors of motivation are a supportive work environment, effective communication, and leadership encouragement, while the inhibiting factors include a lack of training and unclear career development. The study concludes that work motivation positively affects employee productivity, particularly when supported by a clear work system and continuous self-development.